Case Report: Endoscopic radiofrequency ablation with radial-EBUS and ROSE - Zarogoulidis, Paul; Hohenforst-Schmidt, Wolfgang; Papadopoulos, Vasileios; Perdikouri, Eleni-Isidora; Courcoutsakis, Nikolaos; Porpodis, Konstantinos; Matthaios, Dimitrios; Trigonakis, Kostas (Frontiers in Medical Technology, 2023)
Single pulmonary nodules are a common issue in the everyday clinical practice. Currently we have navigation systems with radial-ebus and electromagnetic navigation for obtaining biopsies. Moreover; we have rapid on site evaluation to for quick assessment. These small lesions even when they do not have any clinical significant information with positron emission tomography it is important that are investigated. Radiofrequency and microwave ablation have been evaluated as local treatment techniques. These techniques can be used as therapy for a patient population that cannot be operated. Currently there is one verified operating system used for endoscopic radiofrequency ablation through the working channel of a bronchoscope. We used in our case a new system in order to perform radiofrequency ablation with long term follow up.